Development Web-Based Patient Registration and Queue Management System Using RAD Method with QR Code Verification - Samuel Imanuel Hizkia Saraun; Eliasta Ketaren (Universitas Budi Darma, 2026)
The smoothness of healthcare services, particularly in the registration and queuing processes, is a key factor influencing patient satisfaction. The Bunda Meifa Foundation Clinic, located in Tondano, faces challenges in patient management due to its manual registration process and dynamic doctor schedules. This research aims to design and build a web-based information system that not only provides a user-friendly self-registration interface for patients but also integrates QR Code verification to expedite the check-in process, reduce waiting times, and ease the workload for staff. The system development method used is Rapid Application Development (RAD), which emphasizes a rapid and adaptive development cycle. The developed system offers modern features such as self-service online registration according to available doctor schedules, the creation of a Digital Card with a unique QR Code as proof of appointment, and an innovative